2017
DOI: 10.3390/toxins9080235
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Detection of α-Conotoxin GI in Human Plasma Using a Solid-Phase Extraction Column and LC-MS/MS

Abstract: α-conotoxin GI, a short peptide toxin in the venom of Conus geographus, is composed of 13 amino acids and two disulfide bonds. It is the most toxic component of Conus geographus venom with estimated lethal doses of 0.029–0.038 mg/kg for humans. There is currently no reported analytical method for this toxin. In the present study, a sensitive detection method was developed to quantify GI in human plasma using a solid-phase extraction (SPE) column (polystyrene–divinyl benzene copolymer) combined with liquid chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…To verify the developed methods, the chicken, pork, and beef samples were purchased from the local market in Yangling, Shaanxi Province, China. The samples were extracted in reference to a previous report (Yu et al 2017); briefly, each sample (1-g wet mass) was homogenized and spiked with PMB standards at different concentrations (100, 200, and 500 ng/g). Four milliliters of 0.1% formic acid and 2 mL of methanol were mixed with the tissue sample.…”
Section: Spiked Sample Preparations and Analysismentioning
confidence: 99%
“…To verify the developed methods, the chicken, pork, and beef samples were purchased from the local market in Yangling, Shaanxi Province, China. The samples were extracted in reference to a previous report (Yu et al 2017); briefly, each sample (1-g wet mass) was homogenized and spiked with PMB standards at different concentrations (100, 200, and 500 ng/g). Four milliliters of 0.1% formic acid and 2 mL of methanol were mixed with the tissue sample.…”
Section: Spiked Sample Preparations and Analysismentioning
confidence: 99%
“…The pharmacokinetics of conotoxins in humans are not well described. It has been reported that for α-conotoxin GI, no breakdown was detected after a 3-h incubation in human plasma [165], and for α-conotoxin MII, more than 60% remained after 24 h of incubation in human plasma [166], though the in vivo clearance of these and other conotoxins could be much faster due to metabolism outside of systemic circulation [167]. While modern forensic testing methods are able to detect peptide concentration in plasma of ≈0.1 parts-per-billion [168], it is possible that a conotoxin could metabolize beyond this limit before an autopsy would be performed.…”
Section: Potential Use Of Conotoxins As Bioweaponsmentioning
confidence: 93%